2012
DOI: 10.1002/cncr.27480
|View full text |Cite
|
Sign up to set email alerts
|

Favorable prognosis in patients with T1a/T1bN0 triple‐negative breast cancers treated with multimodality therapy

Abstract: BACKGROUND:The authors evaluated the clinical characteristics, natural history, and outcomes of patients who had 1 cm, lymph node-negative, triple-negative breast cancer (TNBC). METHODS: After excluding patients who had received neoadjuvant therapy, 1022 patients with TNBC who underwent definitive breast surgery during 1999 to 2006 were identified from an institutional database. In total, 194 who had lymph node-negative tumors that measured 1 cm comprised the study population. Clinical data were abstracted, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 21 publications
3
49
1
Order By: Relevance
“…Although TNBC is characterized by an especially poor prognosis, an excellent survival rate has been reported following chemotherapy in a subset of patients with TNBC with early-stage disease (50). Consistent with previous observations, our study also found that patients with TNBC who were lymph node negative, early TNM stage, and low pathologic grade had better DFS and OS rates.…”
Section: Discussionsupporting
confidence: 91%
“…Although TNBC is characterized by an especially poor prognosis, an excellent survival rate has been reported following chemotherapy in a subset of patients with TNBC with early-stage disease (50). Consistent with previous observations, our study also found that patients with TNBC who were lymph node negative, early TNM stage, and low pathologic grade had better DFS and OS rates.…”
Section: Discussionsupporting
confidence: 91%
“…Three retrospective studies have examined the incidence of local failure in TNBC after BCT or mastectomy and found no difference based on surgical procedure, suggesting that these local recurrences are more likely a result of aggressive biology, not residual tumor at the surgical site, which could be improved with wider lumpectomy margins. 29,[37][38][39] This theory is supported by the approximately 40 % decline in IBTR seen in patients with HER2-positive tumors receiving adjuvant systemic trastuzumab and other HER2-targeted agents. 29 In summary, the MP concluded that although there is evidence that the risk of IBTR varies by subtype based on the results of many studies, patients with aggressive tumors remain at equally increased risk for local failure irrespective of treatment with mastectomy or BCT, indicating there is no justification for more widely clear margins over no ink on tumor for any BC subtype.…”
Section: Median Year Of Recruitmentmentioning
confidence: 95%
“…• Also there is chemotherapy treatment which is effective because research shows that the 5-year local recurrence-free survival rate with multimodality therapy was 95% (Ho, 2012).…”
Section: Discussionmentioning
confidence: 99%